A study on the time adjustment of working college students in colleges and universities in Manila - Reyes, Guillermo B. 1916- (1960)
This investigation was conducted in view of helping out working college students with their difficulties in work, leisure, and studies. The researcher believed that the recommendations, which were arrived at after a careful analysis of the comprehensive information and data gathered, from working college students and from the colleges and universities will help alleviate the plight of working college students. Their welfare will directly or indirectly contribute to the general well-being of society.
Thesis (M.A.)--University of the Philippines, Diliman.
Keywords: Student employment; Students -- Philippines -- Manila